KYAI RAJAMALA BOAT’ CANTHIK IN COUTURE BATIK PATTERN - Kristanti, Kristanti; Guntur, Guntur (ISI Press Institut Seni Indonesia Surakarta, 2021)
The Historically, the Javanese palaces relied on boats for transportation, like the Kyai Rajamala boat used by the Surakarta palace. At the time, Paku Buwana IV used the boat to cross the Bengawan Solo river. Kyai Rajamala boat’s canthik is a decorative element on the end bow of the Surakarta palace's boat. Apart from being a decorative element on the boat's end bow, the Kyai Rajamala boat’s canthik is also an heirloom used to ward off bad luck. Because the Kyai Rajamala boat’s canthik has a high value for life, it is critical to communicate the Kyai Rajamala boat’s canthik through easily accepted media. One medium that can convey the beauty of the Kyai Rajamala boat’s canthik is the batik textile art, which can be used to meet basic human needs. Clothing is not only a means of covering the body; it can also be used to convey messages. The Kyai Rajamala boat’s canthik was reinterpreted and dyed with remasol into handmade batik.